2013
DOI: 10.1002/jmv.23638
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny‐based classification of human rhinoviruses detected in hospitalized children with acute lower respiratory infection in Paraguay, 2010–2011

Abstract: Human rhinovirus (HRV), a single-stranded, positive-sense RNA virus, is associated with mild upper respiratory tract infections in children. The aim of this study was to carry out a molecular characterization and phylogeny-based classification of the circulating genotypes of HRV in hospitalized children with clinical manifestations of acute lower respiratory infection in Paraguay. Nasopharyngeal aspirates were collected from 101 children under 5 years of age, hospitalized with symptoms of acute lower respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…This suggests that maternal antibodies are ineffective in preventing RSV infections during infancy, leading to substantial morbidity. HRV, the second most common virus that was detected was prevalent in 25.6% of infants, which is within the range of 0.5-33% [1,7,15,17] as reported by other investigators. Earlier considered as the most common cause of upper respiratory tract infection (URTI), and less commonly less a cause of LRTI, HRV has further established its role also as a common cause of LRTIs among infants [15].…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that maternal antibodies are ineffective in preventing RSV infections during infancy, leading to substantial morbidity. HRV, the second most common virus that was detected was prevalent in 25.6% of infants, which is within the range of 0.5-33% [1,7,15,17] as reported by other investigators. Earlier considered as the most common cause of upper respiratory tract infection (URTI), and less commonly less a cause of LRTI, HRV has further established its role also as a common cause of LRTIs among infants [15].…”
Section: Discussionsupporting
confidence: 88%
“…The numerous negatively selected sites found in the Kenyan HRV strains may indicate that portion of the genome has attained genetic stability and therefore resist deleterious mutations. These findings echo those of previous reports …”
Section: Discussionmentioning
confidence: 99%
“…To date, few data are available on the detection and molecular epidemiology of HRV in Argentina. Only two recent studies carried out in Latin America reported that HRV frequency ranges from 16% to 34%, and described the 3 HRV species in circulation, with HRV-A and C being the most frequent [24,25].…”
Section: Discussionmentioning
confidence: 99%